Clinical characteristics of hoarding disorder in Japanese patients - Masumi Kuwano; Tomohiro Nakao; Koji Yonemoto; Satoshi Yamada; Keitaro Murayama; Kayo Okada; Shinichi Honda; Keisuke Ikari; Hirofumi Tomiyama; Suguru Hasuzawa; Shigenobu Kanba (Heliyon, 2020)
Previous studies have reported clinical characteristics of hoarding disorder (HD), such as early onset, a chronic course, familiality, high unmarried rate, and high rates of comorbidities. However, clinical research targeting Japanese HD patients has been very limited. As a result, there is a low recognition of HD in Japan, leading to insufficient evaluation and treatment of Japanese HD patients.The aim of the current study was to delineate the clinical characteristics of Japanese HD patients. Thirty HD patients, 20 obsessive-compulsive disorder (OCD) patients, and 21 normal controls (NC) were targeted in this study.The HD group had a tendency toward higher familiality, earlier onset, and longer disease duration compared to the OCD group. In addition, the HD group showed a significantly higher unmarried rate than the NC group. The top two comorbidities in the HD group were major depressive disorder (56.7%) and attention-deficit/hyperactivity disorder (26.7%). The HD group had significantly higher scores on hoarding rating scales and lower scores on the Global Assessment of Functioning Scale than the other two groups.The current study showed a clinical trend in Japanese HD patients similar to previous studies in various countries, suggesting that HD may be a universal disease with consistent clinical symptoms.